2013
DOI: 10.1007/s12010-013-0520-8
|View full text |Cite
|
Sign up to set email alerts
|

Extract from Eugenia punicifolia is an Antioxidant and Inhibits Enzymes Related to Metabolic Syndrome

Abstract: The present study aimed to investigate in vitro biological activities of extract of Eugenia punicifolia leaves (EEP), emphasizing the inhibitory activity of enzymes related to metabolic syndrome and its antioxidant effects. The antioxidant activity was analyzed by free radicals scavengers in vitro assays: DPPH·, ABTS(·+), O2(·−), and NO· and a cell-based assay. EEP were tested in inhibitory colorimetric assays using α-amylase, α-glucosidase, xanthine oxidase, and pancreatic lipase enzymes. The EEP exhibited ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…The difference may be due either to that it was important to decrease the total load of toxic phenols below a certain threshold to permit growth or to that the phenols that are most easily oxidized are not the most toxic ones. Previous studies show that some phenols are oxidized more rapidly than others during enzymatic treatment [36] and also that different phenolics have very different toxic effect on the fermenting microorganism [40]. The effect of phenolic compounds on cell growth and BC production of G. xylinus is not well understood and the mechanism of inhibition by phenolic compounds requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The difference may be due either to that it was important to decrease the total load of toxic phenols below a certain threshold to permit growth or to that the phenols that are most easily oxidized are not the most toxic ones. Previous studies show that some phenols are oxidized more rapidly than others during enzymatic treatment [36] and also that different phenolics have very different toxic effect on the fermenting microorganism [40]. The effect of phenolic compounds on cell growth and BC production of G. xylinus is not well understood and the mechanism of inhibition by phenolic compounds requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids, gallic acid, and phytol identified in E . punicifolia leaf extracts have significant antioxidant activity (Galeno et al ., ; Salgueiro et al ., ; Santos et al ., ). It is well known that cells exposed to natural antioxidants exhibit decreased insulin resistance (Ruhe and McDonald, ).…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical studies carried out with the genus Eugenia have demonstrated the occurrence of many classes of constituents including flavonoids, tannins, terpenoids and essentials oils (Oliveira et al, 2006;Galeno et al, 2014). From a pharmacological point of view, studies using crude extracts of this genus showed its anti-inflammatory, analgesic, antifungal, antipyretic, hypotensive, antidiabetic and antioxidant activities (Slowing et al, 1994;Donepudi et al, 2012;Oliveira et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…From a pharmacological point of view, studies using crude extracts of this genus showed its anti-inflammatory, analgesic, antifungal, antipyretic, hypotensive, antidiabetic and antioxidant activities (Slowing et al, 1994;Donepudi et al, 2012;Oliveira et al, 2006). Pharmacological studies of Eugenia punicifolia have shown antioxidant activity (Gonzaga et al, 2007;Galeno et al, 2014), beneficial effects in diabetic rats induced by streptozotocin (Brunetti et al, 2006), increased neurotransmission mediated by nicotinic acetylcholine receptors (Granjeiro et al, 2006) and the release of excitatory catecholamines that could be used to treat patients with Alzheimer's disease (Pascual et al, 2012). Recently, Leite et al (2014) investigated the effects of pentacyclic triterpenes obtained from Eugenia punicifolia on the activation of mechanisms influencing skeletal muscle repair and in vivo muscular tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%